A cyclic allocation model for the inventory-modulated capacitated location problem. Issue 4 (2nd October 2017) - Maass, Kayse Lee; Daskin, Mark S.
ABSTRACT: Hard capacity constraints have been used for decades in facility location modelling and planning. However, such constraints are unrealistic as a variety of operational tools can be used to extend capacity in the short term. To address this, the Inventory-Modulated Capacitated Location Problem (IMCLP) uses inventory as a method of mitigating the hard capacity constraints, but enforces single sourcing. In this paper, we examine a cyclic, day-specific allocation approach to assigning demand sites to processing facilities in the IMCLP. This enables the model to develop a day-of-the-week allocation policy that considers day-to-day variations in the daily processing capacity levels of a set of candidate processing facilities and/or systematic day-to-day demand variations. We demonstrate that allowing demands at a particular site to be allocated to multiple processing facilities in such a manner can be a cost-effective operational tool.